2009
DOI: 10.1111/j.1365-4632.2009.03905.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of serum interleukin‐8 levels in patients with Behcet's disease: high levels may indicate vascular involvement

Abstract: Serum IL-8 levels are increased in the active phase of BD. This marker may be useful in the early detection of vascular involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 29 publications
1
31
1
1
Order By: Relevance
“…These results are in agreement with previous work, which report similar increases in ESR and CRP levels in BD patients 5,6 . Superoxide release was significantly increased in BD patients compared to controls, both at basal conditions and in response to 10 µM fMLP stimulation (Figure 2A).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are in agreement with previous work, which report similar increases in ESR and CRP levels in BD patients 5,6 . Superoxide release was significantly increased in BD patients compared to controls, both at basal conditions and in response to 10 µM fMLP stimulation (Figure 2A).…”
Section: Discussionsupporting
confidence: 94%
“…Once secreted, IL-1 and TNF-α activate vascular endothelium, leading to increased expression of E-selectin and P-selectin in BD 4 , which function as receptors for leukocyte adhesive proteins. IL-1, TNF-α, and IL-6 also activate hepatocytes to synthesize acute-phase proteins, which are also elevated in BD patients 5,6 . The activation state of neutrophils in BD patients is also evident by the expression of several surface antigens and levels of circulating proteins released by neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…Autoantibodies, binding molecules exposed on the surface of neurons, lead to a neurotoxic effect [1,30]. Increased levels of TNF, IL-6 [31], IL-18 [32] and IL-8 have been reported in cultures of monocytes from people with BD [33,34]. IL-8 in particular attracts and activates neutrophils and other leukocytes and is thought to mediate endothelial damage in BD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ambrose et al demonstrated significantly higher production of CXCL10/IP10 in blood monocytes of BD patients stimulated with IFNγ compared to HC, rheumatoid arthritis, and systemic lupus erythematosus controls [170]. There is even more robust evidence for CXCL8/IL8, a potent neutrophil chemoattractant, being implicated in BD pathogenesis, with some of the authors proposing that it could be a marker for vascular involvement and a more reliable marker for disease activity than the C-reactive protein or erythrocyte sedimentation rate [171][172][173][174].…”
Section: Chemokinesmentioning
confidence: 99%